Penggunaan Media Pembelajaran Konkret Untuk Meningkatkan Hasil Belajar Matematika bagi Siswa Tunagrahita Kelas X SLB GMIM Nazareth Tuminting - Naomi Onsu (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of the research that the author conducted was: to determine the effect of the use of concrete media on improving mathematics learning outcomes for mentally retarded children in class X at SLB GMIM Nazareth Tuminting. The type of research used is Classroom Action Research (CAR) which aims to find solutions to social problems that develop in society. This research data was collected from various sources which include information from students, observations in the teaching and learning process conducted by observers, documents or archives in the form of curriculum, student test results in the form of grades. After the implementation of two cycles in this study, the final findings showed that the students of class X, had been able to improve the difficulties in learning mathematics, especially understanding the measurement of time. Based on the results of observations and learning actions taken, it can be concluded that the mathematics learning activities that have been carried out on measuring time about the movement of the clock hands and determining the time signature by using the clock model can improve student learning outcomes. From the initial study only 1 child completed learning from 4 students. while in the first cycle it reached 2 students or 50%. The level of mastery of mathematics can be increased through the use of clock model props which are larger in size and different in color from the first cycle. The level of complete learning in the second cycle reached 4 students or 100%.